SELF-CARE MANAGEMENT AND QUALITY OF LIFE IN HEMODIALYSIS PATIENTS - Herawati, Leli; Wahyuni, Sri; Ananda, Ichfad; Hasibuan, Nur Suci (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2025)
Hemodialysis is a procedure that removes solutes and excess fluids from the blood. Its main goal is to relieve symptoms by controlling uremia, fluid overload, and electrolyte imbalances in patients with chronic kidney disease. Hemodialysis also requires patients to make significant lifestyle adjustments. This study aims to examine the relationship between self-care management and the quality of life among hemodialysis patients. This quantitative study used a cross-sectional design with a total sampling technique involving 23 respondents. Data were collected using a Self-Care Management Questionnaire and the KDQOL (Kidney Disease Quality of Life) instrument. The data were analyzed using the Gamma test. The findings showed a significant relationship between self-care management and quality of life among hemodialysis patients at the Hemodialysis Unit of Sinar Husni Hospital, Medan, in 2025. The chi-square test result showed a p-value of 0.000 (<0.05), indicating a significant association. There is a significant relationship between self-care management and the quality of life of hemodialysis patients at Sinar Husni Hospital, Medan.